2015
DOI: 10.1002/jbm.b.33486
|View full text |Cite
|
Sign up to set email alerts
|

Degradable poly(apigenin) polymer inhibits tumor cell adhesion to vascular endothelial cells

Abstract: Cancer and the inflammatory system share a complex intertwined relationship. For instance, in response to an injury or stress, vascular endothelial cells will express cell adhesion molecules as a means of recruiting leukocytes. However, circulating tumor cells (CTCs) have been shown to highjack this expression for the adhesion and invasion during the metastatic cascade. As such, the initiation of endothelial cell inflammation, either by surgical procedures (cancer resection) or chemotherapy can inadvertently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Apigenin-loaded lipid nanocapsules prepared with phase inversion method showed high efficacy in restricting breast and liver cancer growth [237]. Cochran et al [238] demonstrate that a long-term releasing apigenin-based polymer and subsequent nanoparticle delivery system has ability to inhibit tumor cell adhesion through the suppression of endothelial cell adhesion molecule expression. These studies show promise that nano-formulations of apigenin could become an effective drug-delivery system.…”
Section: 0 Major Limitations Of Apigeninmentioning
confidence: 99%
“…Apigenin-loaded lipid nanocapsules prepared with phase inversion method showed high efficacy in restricting breast and liver cancer growth [237]. Cochran et al [238] demonstrate that a long-term releasing apigenin-based polymer and subsequent nanoparticle delivery system has ability to inhibit tumor cell adhesion through the suppression of endothelial cell adhesion molecule expression. These studies show promise that nano-formulations of apigenin could become an effective drug-delivery system.…”
Section: 0 Major Limitations Of Apigeninmentioning
confidence: 99%
“…Apigenin has demonstrated suppression of cancer signalling pathways and tumour cell adhesion on endothelial cells. Signalling pathways thought to be involved include JNK, ERK and AP‐1 . In other research studies, apigenin has exhibited anti‐inflammatory effects and demonstrated benefit in metabolic syndrome via inhibition of the enzyme NAD+ase .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of blood pressure reduction and vasodilation, research has indicated that apigenin can dilate the contracted aortic ring of rats caused by phenylephrine in vitro . Experiments have shown that apigenin can inhibit the proliferation of vascular smooth muscle cells in a dose-dependent manner within a certain concentration range (17), suggesting that apigenin is important in preventing cardiovascular diseases such as hypertension and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the antioxidant effect of apigenin and its role in protecting vascular endothelial cells occurred by increasing the activity of intracellular superoxide dismutase (SOD) and the secretion of NO. In addition, apigenin can inhibit the proliferation of vascular smooth muscle cells in a dose-dependent manner and may have the potential to inhibit thickening of vascular walls (17). …”
Section: Introductionmentioning
confidence: 99%